Method for manufacturing electrocatalyst for alkaline water electrolysis
By preparing a combined layer of Ni or Ni alloy and graphene and graphite particles in an electrochemical electrolyte in an electrochemical electrolyte and co-depositing of a combined layer of Ni or Ni alloy and graphene particles in an electroplating bath, the problem of high cost and difficulty in mass production in the prior art is solved, and low-cost and efficient electrocatalyst production is achieved, which is suitable for industrial-scale alkaline water electrolysis.
Patent Information
- Application Number
- CN202380055515.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-05
- Filing Date
- 2023-06-05
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is costly and difficult to produce on a large scale when manufacturing electrocatalysts for alkaline water electrolysis, which affects industrial applications.
An aqueous electrolyte containing a suspended graphene and graphite nanosheet structure was prepared in an electrochemical electrolytic cell, and a combined layer of Ni or Ni alloy and graphene and graphite particles were co-deposited in an electroplating bath to form an alkaline water electrolytic electrolytic electrocatalyst.
It has achieved low-cost large-scale production of electrocatalysts, improved electrocatalytic activity, is suitable for industrial-scale alkaline water electrolysis, and is economical and affordable.
Smart Images

Figure CN119604469A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing an electrocatalyst for alkaline water electrolysis. The present invention also relates to an electroplating bath for use in the method. Furthermore, the present invention relates to an alkaline water electrolysis device incorporating an electrocatalyst obtainable by the method. Background Art
[0002] The production of hydrogen and oxygen from water by water electrolysis is a recognized technological process worldwide. The three related processes for water electrolysis differ in the electrolyte used, i.e., alkaline electrolysis using liquid alkaline electrolytes, acidic PEM electrolysis using proton-conducting polymer electrolyte membranes, and high-temperature electrolysis using solid oxide electrolytes.
[0003] The most commonly used technology for water electrolysis is by alkaline electrolysis, which is characterized by high efficiency and affordable price. The purity of hydrogen obtained by electrolysis using this type of equipment is very high and is in the range of about 99.0% to 99.7%. A typical electrolyzer of this type consists of two electrodes immersed in an electrolyte and separated by a membrane. The role of the solution is to maximize the ionic conductivity. It mainly contains KOH. The operating temperature of this process is about 40°C-90°C. NaCl or NaOH solutions can also be used as electrolytes, but they are less common. In this type of device, water is located on both sides of the electrodes with the electrolyte. The cathode and the anode are separated by a thin polymer membrane. The membrane is penetrated by OH- ions, which are produced by the reaction occurring at the cathode. Hydrogen is obtained from the cathode and water, and a small amount of oxygen is obtained from the anode.
[0004] Electrocatalysts for alkaline electrolysis are a well-developed technology. In recent decades, with the development of nanotechnology, new research trends can be observed in order to further develop electrocatalysts. In theory, the best electrocatalyst available is platinum, but due to its extremely high cost, it is not a preferred candidate for industrial-scale water electrolysis. Traditionally, the most widely used electrode materials for alkaline electrolysis are nickel and its alloys, due to their stability and favorable activity in alkaline conditions. However, the main problem is the deactivation of the catalyst over time, due to the high concentration of hydrogen in the cathode side, nickel hydride is formed at the surface. Recent research has focused on using a multi-catalyst system with regulated chemical and physical properties to stabilize the nickel catalyst to prevent deactivation. Recently, with the support of new nanotechnology developments, new nanostructured electrocatalyst concepts have emerged. The main purpose is to increase the surface area and provide unique catalytic properties for the evolution reactions (HER and OER) of hydrogen and oxygen.
[0005] HER on Ni with graphene or graphene oxide has been studied for use in alkaline solutions. Studies have shown that the electrocatalytic activity of these composites is greatly enhanced compared to Ni alone. The enhanced electroactivity of these composites is explained by good electrical conductivity, large specific surface area, and high hydrogen adsorption / desorption activity.
[0006] Graphene can be prepared by mechanical stripping, molecular assembly, chemical vapor deposition (CVD) method and electrochemical method from carbon source. Graphene produced using electrochemical method can have relatively high quality, with minimum hole defects and adjustable oxidation level. In the art, graphene or graphite nanosheet structure produced by electrochemical stripping is usually separated from electrolyte by multiple separation techniques, and the separation technique includes filtering, centrifugal force to precipitate graphene or graphite nanosheet structure, collect graphene or graphite nanosheet structure and sedimentation at the interface of two immiscible solvents. The graphene or graphite nanosheet structure of electrochemical stripping can be further processed after stripping. For example, ultrasonic energy and other techniques known to those skilled in the art can be used to further strip material, to reduce the number of flake size and graphene layers. At present, the large commercial availability of graphene is limited, and the cost is very high, for example, the typical price range of 1 gram of commercial grade pure, 3nm filtered graphene nano powder is about 200-400 euros.
[0007] The challenge of increasing the production volume of these advanced materials for large-scale and cost-effective (eg, ideally using only abundant materials) electrode construction remains substantial. Summary of the invention
[0008] It was therefore an object of the present invention to provide a cost-effective process for producing electrocatalysts for alkaline water electrolysis.
[0009] This and other objects as well as further advantages are met or exceeded by the present invention, which provides a method according to claim 1, an electroplating bath according to claim 12 and an alkaline water electrolysis device according to claim 14, as well as preferred embodiments in the dependent claims.
[0010] To achieve this object, the present invention provides in a first aspect a method for producing an electrocatalyst for alkaline water electrolysis, the method comprising the following steps:
[0011] (i) preparing an aqueous electrolyte 1 comprising suspended graphene and graphite nanosheet structures having a thickness of <100 nm, preferably <50 nm, in an electrochemical cell (cell 1), wherein the cell comprises: (a) a negative electrode of graphite, (b) a positive electrode of graphite, (c) an aqueous electrolyte comprising ions in a solvent, wherein the ions comprise cations and anions, wherein the anions comprise sulfate anions; and wherein the method comprises the step of passing an electric current through the cell to obtain exfoliated graphene and graphite nanosheet structures in the aqueous electrolyte in an amount greater than 5 g / l, and more preferably greater than 10 g / l;
[0012] (ii) composing an electroplating bath 2 comprising suspended graphene and graphite nanoplatelet structures in an amount greater than 2 g / l, preferably greater than 5 g / l and more preferably greater than 10 g / l, having a thickness of <100 nm, said electroplating bath 2 comprising an aqueous solution 3 of nickel sulfate and the aqueous electrolyte 1 of process step (i) comprising suspended graphene and graphite nanoplatelet structures in an amount greater than 5 g / l, preferably greater than 10 g / l, having a thickness of <100 nm; and
[0013] (iii) electrodepositing a combined layer of Ni or Ni-alloy and graphene and graphite particles from the electroplating bath 2 on the support to form an alkaline water electrolysis electrocatalyst.
[0014] In the electrochemical exfoliation of step (i), as sulfate intercalation proceeds, graphite evolves into graphene and graphite nanosheet structures having a thickness of <100 nm, preferably less than 50 nm, and more preferably less than 20 nm.
[0015] The term "nanosheet" refers to substantially flat graphene or graphite particles having a nanometer-scale thickness (z), typically less than 100 nm, preferably less than 50 nm, more preferably less than 20 nm, and lateral dimensions (x, y) greater than the thickness.
[0016] The key feature of the present invention is that both the negative and positive electrodes used for electrochemical stripping are graphitic, resulting in high yields of graphene and graphite nanosheet structures. The method is scalable to allow large-scale production of graphene and graphite nanosheet structures. It is not necessary to use electrolytes composed of complexes to establish stripping, thereby avoiding the need for, for example, organic ions, Li ions, Mg ions, which would otherwise increase the component complexity of the electrochemical stripping process, with corresponding increases in safety requirements, costs, process waste and by-product disposal.
[0017] Another key feature of the present invention is that the aqueous electrolyte 1 and the aqueous solution 3 each contain sulfate as one of its main components, wherein the aqueous solutions 1, 3 are compatible and can be easily mixed into a Ni or Ni-alloy electroplating bath 2, preferably an acidic electroplating bath, without any technical difficulties or chemical disadvantages, the electroplating bath having suspended graphene and graphite nanosheet structures in an amount greater than 2g / l, preferably greater than 5g / l, and more preferably greater than 10g / l, having a thickness of <100nm. This avoids the need to separate the graphene and graphite nanosheet structures from the aqueous electrolyte 1, thereby saving a lot of cost and processing time. The aqueous electrolyte 1 can be directly used as a raw material for constituting the electroplating bath 2.
[0018] The method of the present invention is a simple method, using readily available components that have been accepted by the chemical and metallurgical industries. The method can be scaled up to industrial scale and can be operated in a continuous manner. The resulting electrocatalyst can be manufactured on a large scale, i.e., on a square meter and larger scale. The resulting electrocatalyst can be produced in large quantities at a relatively low cost.
[0019] The present inventors have found that Ni electrodeposition in 1M KOH in combination with graphene or graphite particles using 1.0 cm 2 The hydrogen evolution reaction (HER) after three voltammetric cycles of the effective geometric surface area is very close to that of platinum, making the resulting electrocatalyst suitable for alkaline water electrolysis, also for industrial scale alkaline water electrolysis. Compared with rare earth metals and other metals such as platinum, cobalt, iridium and molybdenum that are used for their catalytic ability, Ni is a much more abundant material.
[0020] Compared to some very small-scale scientific or academically produced electrocatalysts, it may have a slightly lower catalytic capacity or efficiency, but on the other hand it can be produced in large quantities at low cost, making the electrocatalyst obtained by the present invention very suitable and economically attractive for use in industrial-scale alkaline water electrolysis.
[0021] In one embodiment, a 2 SO 4 , K 2 SO 4 and (NH 4 ) 2 SO 4 The aqueous electrolyte of inorganic salt 1 was used as the main source of sulfate anions for electrochemical stripping. The use of sulfate anions resulted in efficient stripping, while for example NH 4 Cl or NaNO 3 Very poor exfoliation occurred and thus the product yield was very low.
[0022] In one embodiment, electrochemical stripping is performed using an aqueous electrolyte 1 having a concentration of sulfate ions in the range of 0.4 to 3M, preferably in the range of 0.4 to 1.3M.
[0023] In a preferred embodiment, electrochemical stripping uses a sodium sulfate (Na 2 SO 4 ) is carried out with an aqueous electrolyte 1. Sodium sulfate is a commonly accepted component in the chemical industry and is readily available at a reasonable cost. Sodium sulfate is also compatible with the subsequently constituted electroplating bath for co-deposition of Ni or Ni alloys, and the graphite evolves into graphene and graphite nanosheet structures having a thickness of <100 nm, preferably <50 nm. Preferably, sodium sulfate is present in a concentration in the range of 0.4 to 3 M, more preferably in the range of 0.4 to 1.3 M, and most preferably in the range of 0.5 to 1 M.
[0024] Good results can be obtained when the operating parameters of the electrochemical cell for electrochemical exfoliation of graphene and graphite nanosheets include one or more of the following:
[0025] The operating cell temperature is about 10-90°C, preferably about 20-70°C, more preferably about 40-65°C;
[0026] pH value in the range of about 1 to 5, preferably about 2 to 4;
[0027] The current density is about 30-100A / dm 2 , preferably 60-90A / dm 2 ;
[0028] The voltage is between 10 and 40V, preferably between 15 and 40V.
[0029] The working potential of the electrolyzer is at least the standard potential for reductive intercalation. An overpotential can be used to increase the reaction rate and drive cations into the graphite gallery at the negative electrode. Preferably, an overpotential of about 1mV-10V is used, more preferably an overpotential of about 1mV-5V, relative to a suitable reference known to those skilled in the art. In an electrolyzer with only two terminals and no reference, a larger potential can be applied across the electrodes, but a significant amount of potential drop will occur with the electrolyzer resistance, rather than acting as an overpotential at the electrode. In these cases, the applied potential can be at most about 20V or at most about 40V.
[0030] The voltage applied across the electrodes can be cyclic or swept. In one embodiment, both electrodes are graphite and the potential is swept so that the electrodes change from positive to negative and vice versa. In this embodiment, cationic exfoliation will occur on both electrodes, depending on the polarity of the electrodes during the voltage cycle. In some embodiments, alternating current can be used to allow rapid intercalation and deintercalation.
[0031] The current density at the negative electrode is controlled by a combination of the surface area of the electrode and the overpotential used. The method can also be performed under current control.
[0032] The key feature of the present invention is that both the negative electrode and the positive electrode for electrochemical stripping are graphite, resulting in a high yield of graphene and graphite nanosheet structures. A wide range of carbon materials can be used, including natural graphite sheets, artificial graphite, highly ordered pyrolytic graphite (HOPG), pitch-based graphite, carbon rods, amorphous carbon, and raw materials disclosed in patent document US2018 / 0179648-A1 published on June 28, 2018, which is incorporated herein by reference.
[0033] In one embodiment, the suspended graphene and graphite nanosheet structures (thickness <100 nm, preferably <50 nm, more preferably <20 nm) in electrolyte 1 are subjected to high shear mixing as known in the art to obtain a homogenous suspension, and which may enable some further exfoliation.
[0034] In one embodiment, the suspended graphene and graphite nanosheet structures in the electrolyte 1 are further exfoliated by using ultrasonic treatment, which has a thickness of <100nm, preferably <50nm, more preferably <20nm. The ultrasonic treatment is preferably carried out at an energy level of 10-200Wh per gram of the exfoliated graphene and graphite obtained in process step (i). More preferably, the ultrasonic treatment is carried out at an energy level of 10-100Wh per gram. The ultrasonic treatment is carried out using equipment for treating liquids such as a commercial sonicator, wherein an ultrasonic generator (sonotrode) immersed in the liquid is used to transmit acoustic energy to the system by cavitation (i.e., the formation and explosion of bubbles), the wave frequency is about 24kHz, and the power is defined as above.
[0035] The electroplating bath 2 for co-depositing a combined layer of Ni or Ni alloy and graphene and graphite particles on a support is composed of: (a) an aqueous electrolyte 1 containing sulfate anions and having a structure of suspended graphene and graphite nanosheets, and (b) an aqueous solution 3 of nickel sulfate suitable for electrodepositing Ni or Ni-alloy particles on a substrate or support. Since the aqueous electrolyte 1 and the aqueous solution 3 each contain sulfate as one of their main components, the aqueous solutions 1, 3 are compatible and can be mixed into the electroplating bath 2 without any technical difficulties or disadvantages.
[0036] The aqueous mixture 3 containing nickel sulfate forms the main source for co-deposition by electroplating a combined layer of Ni or Ni alloy with graphene and graphite particles on a support or substrate.
[0037] In a preferred embodiment, the aqueous solution 3 comprises nickel sulfate, nickel chloride and preferably boric acid. In a more preferred embodiment, the aqueous solution 3 comprises 10-400 g / l nickel sulfate (Na 2 SO 4 )、10-150g / l nickel chloride (NiCl 2 ) and 5-100 g / l boric acid (H 3 BO 3 ). This aqueous solution 3 is also known in the art as a Watt bath, has very good scalability and is used for electroplating metal substrates with Ni or Ni alloy layers on an industrial scale, such as for nickel-plated battery casings. The Watt bath is also used on a continuous industrial scale, and therefore not only for batch processes.
[0038] In one embodiment, the aqueous solution 3 comprises nickel sulfate, nickel chloride and citrate-gluconate. In a more preferred embodiment, the aqueous solution 3 comprises 100-300 g / l nickel sulfate, 10-80 g / l nickel chloride, 10-70 g / l ammonium sulfate ((NH 4 ) 2 SO 4 ), 50-200 g / l sodium citrate and 10-50 g / l sodium gluconate. The sodium citrate prevents the formation of solid compounds (nickel salts) in the bath and acts as a pH buffer. This aqueous solution 3 is usable, but from a chemical point of view it is more complex than the Watt bath and therefore it is less preferred.
[0039] In an electroplating bath 2 comprising nickel sulfate as one of its main components, a combined layer of Ni or a Ni-alloy is electroplated on a support or substrate together with graphene and graphite to form an electrocatalyst.
[0040] Good results can be obtained when the operating parameters in the electroplating process for deposition include one or more of the following:
[0041] - the bath temperature is in the range of about 20-70°C, preferably about 40-65°C;
[0042] - pH in the range of 1-5, preferably 2-5, more preferably 2-4;
[0043] -About 0.2-10.0A / dm 2 , preferably about 0.5-5.0A / dm 2 The current density;
[0044] - electroplating time 1 to 400 seconds, preferably 20 to 200 seconds, more preferably 20 to 150 seconds;
[0045] - The composition of the electroplating bath 2 comprises:
[0046] - 10-400 g / l nickel sulfate, preferably 200-300 g / l nickel sulfate;
[0047] - 10-150 g / l nickel chloride, preferably 30-60 g / l nickel chloride;
[0048] - optionally 5-100 g / l boric acid, preferably 20-50 g / l boric acid; and
[0049] at least 2 g / l, preferably at least 5 g / l, more preferably at least 10 g / l of graphene and graphite nanoplatelet structures having a thickness of <100 nm, preferably <50 nm, more preferably <20 nm, and originating from the aqueous electrolyte 1 obtained from process step (i).
[0050] Some gentle bath agitation may be applied to keep the nanosheet structures suspended. The bath composition may have a low concentration of reagents to prevent coagulation of the suspended graphene and graphite nanosheet structures. Suitable reagents are methyl pyrrolidone, dimethyl sulfoxide and anthraquinone-diazonium salts, or cationic surfactants. In addition to the presence of graphene and graphite nanosheet structures (thickness <100 nm), this electroplating process using these operating parameters is generally referred to in the art as a Watt process.
[0051] The use of these operating parameters produces an electrocatalyst suitable for alkaline water electrolysis. The electroplating process uses readily available chemical components that are well known and accepted in the chemical and metallurgical industries. The method can be operated as a batch process. However, a further advantage is that it can be operated as a continuous process, enabling the production of large quantities of electrocatalyst materials suitable for alkaline water electrolysis in both quantity and surface area.
[0052] In one embodiment, the combined layer of Ni or Ni alloy and graphene and graphite particles electrodeposited from electroplating bath 2 on the support to form the electrocatalyst has a thickness of at least about 0.1 μm, preferably at least about 0.5 μm.
[0053] The support or deposition substrate does not limit the present invention and can be any material used in the art for anode materials in alkaline water electrolysis, such as nickel sheet or cold rolled carbon steel (such as any one of DC01 to DC07 grades) or stainless steel (such as 904L or 905L), and preferably, the metal substrate is provided with a thin nickel layer.
[0054] In another aspect, the present invention is embodied in an electroplating bath 2 constituted in step (ii) of the inventive method as described and claimed herein. The plating bath 2 comprises graphene and graphite nanoplatelet structures having a thickness of <100 nm, preferably <50 nm, more preferably <20 nm. The amount of these graphene and graphite nanoplatelet structures is greater than 2 g / l, preferably greater than 5 g / l, and more preferably greater than 10 g / l.
[0055] Such an electroplating bath 2 comprising said graphene and graphite nanoplatelet structures of defined size and concentration and constituted according to the invention can advantageously be sold independently of the process.
[0056] In one embodiment of the electroplating bath 2, it contains nickel sulfate as one of its main components.
[0057] In one embodiment, the electroplating bath 2 has a pH of 1 to 5, preferably 2 to 5, more preferably 2 to 4.
[0058] In one embodiment of the electroplating bath 2, it comprises:
[0059] - 10-400 g / l nickel sulfate, preferably 200-300 g / l nickel sulfate; and
[0060] - 10-150 g / l nickel chloride, preferably 30-60 g / l nickel chloride; and
[0061] - Optionally 5-100 g / l boric acid, preferably 20-50 g / l boric acid.
[0062] In another embodiment, the electroplating bath 2 comprises 100-300 g / l nickel sulfate, 10-80 g / l nickel chloride, 10-70 g / l ammonium sulfate (NH 4 ) 2 SO 4 ), 50-200 g / l sodium citrate, and 10-50 g / l sodium gluconate.
[0063] In another aspect, the present invention also embodies an alkaline water electrolysis device comprising at least one electrocatalyst obtainable by the method according to the present invention. In one embodiment, the alkaline water electrolysis device has 6 or more electrocatalyst plates, and preferably 10 or more electrocatalyst plates. Typically the electrocatalyst plates are spaced about 1-5 cm apart from each other. In one embodiment, each electrocatalyst plate in the alkaline water electrolysis device has at least about 0.5 m 2 (e.g., having a board size of 10×50 cm or 20×50 cm), and preferably at least about 1.5 m 2 surface area.
[0064] The invention will now be illustrated with reference to the non-limiting comparative and exemplary embodiments of the invention. Example
[0065] According to the invention, two suspensions of exfoliated graphene and graphite nanoplatelets were produced using an electrochemical cell having a positive and a negative electrode made either of graphite SGL sheets Sigraflex or both made of solid graphite rods (from Atotech). The electrochemical cell conditions were: volume 3000 ml, 0.75 M sodium sulfate, current density 45 A / dm 2 , voltage 31 V, temperature 50-55° C., treatment time 4 hours. This resulted in two solutions with about 8.4 g / l of graphene and graphite nanosheets (with a thickness of <100 nm) based on graphite SGL plate Sigraflex electrodes, and about 14.7 g / l of graphene and graphite nanosheets (with a thickness of <100 nm) based on solid graphite rod electrodes.
[0066] Based on these two suspensions, two acidic electroplating baths have been constructed according to the invention, namely:
[0067] Electroplating solution 1: 1000 ml suspension with about 8.4 g / l graphene and graphite nanoplatelets (with a thickness of <100 nm) based on graphite SGL plates Sigraflex electrodes, and 250 g nickel sulfate hexahydrate, 50 g nickel chloride hexahydrate and 30 g added boric acid.
[0068] Electroplating solution 2: 1000 ml suspension with about 14.7 g / l graphene and graphite nanoplatelets (with a thickness of <100 nm) based on solid graphite rod electrodes, and 250 g nickel sulfate hexahydrate, 50 g nickel chloride hexahydrate and 30 g added boric acid.
[0069] Based on these two electroplating baths according to the invention, combined layers of nickel and graphene and graphite nanoplatelet structures have been deposited on a support made of Ni-plated carbon steel having dimensions of 100×100 mm, which had been pretreated by degreasing and desmutting as known in the art. For both baths, the same plating conditions were used, namely 50° C., a current density of 5 A / dm 2 , a plating time of 120 seconds and resulted in complete coverage of the support surface with a layer thickness of 2 μm.
[0070] The presence of nanometer-sized multilayer graphene flakes has been confirmed by Raman spectroscopy and shows a mixture of graphene and graphene oxide.
[0071] In addition, three comparative acidic electroplating baths or solutions were prepared for electrodeposition of combined layers of Ni and other nano-sized particles on the support. These comparative baths were based on references showing that these have high catalytic activity. These baths were purposely supplemented with graphite powder, SiC powder and MoS 2 Powder; based on commercially available powder. The compositions of the three plating baths are:
[0072] Comparative bath 1: 1000 ml of demineralized water, plus 250 g of nickel sulfate hexahydrate, 50 g of nickel chloride hexahydrate, 30 g of boric acid, and 20 g of pure graphite powder (natural, microcrystalline grade, APS2-15 microns, 99.9995% (metal basis), UCP-1-M grade, super "F" purity, Lot: 61200828, ThermoFischer (Kandel) GmbH). The suspension was mixed for 2 hours using a high shear mixer.
[0073] Comparative Bath 2: 1000 ml demineralized water, plus 250 g nickel sulfate hexahydrate, 50 g nickel chloride hexahydrate, 30 g boric acid, and 20 g silicon carbide (SiC) powder (β phase, nano powder, 45-45 nm APS powder, SA.70-90 nm 2 / g, Lot: R21E078, ThermoFischer (Kandel) GmbH). The suspension was mixed for 2 hours using a high shear mixer.
[0074] Comparative Bath 3: 1000 ml of demineralized water, plus 250 g of nickel sulfate hexahydrate, 50 g of nickel chloride hexahydrate, 30 g of boric acid, and 20 g of molybdenum disulfide (MoS 2 ) powder (98%, 325 mesh powder). The suspension was mixed with a high shear mixer for 2 hours.
[0075] Based on these three baths, Ni and C or SiC or MoS 2 The combined layer of particles was deposited on a support made of nickel-plated carbon steel having dimensions of 100×100 mm and pre-treated by degreasing and desmearing as known in the art. The same plating conditions were used for all three plating baths, namely 50° C., a current density of 5 A / dm 2 , a plating time of 120 seconds and resulted in complete coverage of the support surface with a layer thickness of 2 μm.
[0076] After three voltammetric cycles in 1.0 M KOH solution, 1.0 cm 2 The effective geometric surface area, hydrogen evolution reaction (HER) of the materials electrodeposited from plating bath 2 and comparative baths 1-3 was evaluated. The samples have been tested against bare nickel-plated support material and platinum sheets. The results are shown in Figure 1A and 1B middle.
[0077] exist Figure 1A In the figures, the results for a plating bath 2 according to the invention for a bare nickel-plated support and for platinum are given. Figure 1B The results comparing Baths 1, 2 and 3 for platinum are shown in .
[0078] from Figure 1A and Figure 1B From the results, it can be seen that the graphene curve of the inventive electroplating bath 2 shows significantly higher HER activity than the comparative bath 2 with pure graphite powder. In addition, it can be seen that the shape of the graphene curve (made according to the present invention) is almost the same as that of platinum, so the catalytic activity of the graphene-coated sample is expected to be almost comparable to that of platinum.
[0079] Therefore, the electrocatalyst produced according to the present invention may have a slightly lower catalytic capacity or efficiency compared to platinum, but on the other hand, it can be produced in large quantities at low cost, making the obtained electrocatalyst very suitable and economically attractive for use in alkaline water electrolysis on an industrial scale.
[0080] Now that the invention is fully described, it will be apparent to one skilled in the art that many changes and modifications can be made without departing from the spirit or scope of the invention as described herein.
Claims
1. A method for producing an electrocatalyst for alkaline water electrolysis, the method comprising the following steps: (i) preparing an aqueous electrolyte (1) in an electrochemical cell, the aqueous electrolyte comprising suspended graphene and graphite nanosheet structures having a thickness of <100 nm, wherein the cell comprises: (a) a negative electrode of graphite, (b) a positive electrode of graphite, (c) an aqueous electrolyte comprising ions in a solvent, the ions comprising cations and anions, wherein the anions comprise sulfate anions; and wherein the method comprises the step of passing an electric current through the cell to obtain exfoliated graphene and graphite nanosheet structures in the aqueous electrolyte in an amount greater than 5 g / l, and preferably at least 10 g / l; (ii) forming an electroplating bath (2) comprising suspended graphene and graphite nanoplatelet structures having a thickness of <100 nm in an amount of greater than 2 g / l, said electroplating bath (2) comprising an aqueous solution of nickel sulfate (3) and the aqueous electrolyte (1) of step (i) comprising suspended graphene and graphite nanoplatelet structures having a thickness of <100 nm in an amount of greater than 5 g / l, preferably at least 10 g / l; (iii) electrodepositing a combined layer of Ni or Ni alloy and graphene and graphite particles from the electroplating bath (2) to form an electrocatalyst, preferably an alkaline water electrolysis electrocatalyst, on a support.
2. The method according to claim 1, wherein the aqueous electrolyte (1) comprises sulfate anions from an inorganic salt selected from the group consisting of Na2SO4, K2SO4 and (NH4)2SO4.
3. The method according to claim 1 or 2, wherein the aqueous electrolyte (1) comprises 0.4 to 3M, preferably 0.4 to 1.3M, sulfate anions.
4. The method according to any one of claims 1 to 3, wherein the aqueous electrolyte (1) comprises sulfate anions from sodium sulfate, and preferably in the range of 0.4 to 3M, and preferably in the range of 0.4 to 1.3M.
5. The method according to any one of claims 1 to 4, wherein the aqueous solution (3) comprises nickel sulfate and nickel chloride.
6. The method according to any one of claims 1 to 5, wherein the aqueous solution (3) comprises nickel sulfate, nickel chloride and boric acid.
7. The method according to any one of claims 1 to 6, wherein the aqueous solution (3) comprises 10-400 g / l nickel sulfate, 10-150 g / l nickel chloride and optionally 5-100 g / l boric acid.
8. The method according to any one of claims 1 to 7, wherein the electroplating bath (2) comprises an aqueous solution (3) containing nickel sulfate and an aqueous electrolyte (1) comprising suspended graphene and graphite nanosheet structures having a thickness of <100 nm in an amount greater than 5 g / l, preferably greater than 10 g / l.
9. The method according to any one of claims 1 to 8, wherein the electroplating bath (2) comprises 10-400 g / l nickel sulfate, 10-150 g / l nickel chloride, optionally 5-100 g / l boric acid, and an amount of graphene and graphite nanoplatelet structures having a thickness of <100 nm in an amount greater than 2 g / l, preferably greater than 5 g / l.
10. The method according to any one of claims 1 to 9, wherein the electrodeposition from the electroplating bath (2) has one or more of the following operating parameters: bath temperature in the range of 20-70°C, preferably 40-65°C; a pH in the range of 1 to 5, preferably 2 to 5; Current density 0.2-10.0A / dm 2 , preferably 0.5-5.0A / dm 2 ; The electroplating time is 1 to 400 s, preferably 20 to 200 s.
11. The method according to any one of claims 1 to 10, wherein the combined layer of Ni or Ni alloy and graphene and graphene particles electrodeposited on the support in step (iii) has a thickness of at least 0.1 μm, and preferably at least 0.5 μm.
12. The electroplating bath (2) constituted in step (ii) according to any one of claims 1 to 9, having an amount of suspended graphene and graphite nanoplatelet structures having a thickness of <100 nm in an amount greater than 2 g / l, said electroplating bath (2) comprising (a) an aqueous solution of nickel sulfate (3) and (b) an aqueous electrolyte (1) obtained in step (i), the aqueous electrolyte comprising an amount of suspended graphene and graphite nanoplatelet structures having a thickness of <100 nm in an amount greater than 5 g / l, preferably at least 10 g / l.
13. The electroplated coating of claim 12, comprising 10-400 g / l nickel sulfate, preferably 200-300 g / l nickel sulfate; 10-150 g / l nickel chloride, preferably 30-60 g / l nickel chloride; and Optionally 5-100 g / l boric acid, preferably 20-50 g / l boric acid.
14. An alkaline water electrolysis device comprising an electrocatalyst obtainable by a method according to any one of claims 1 to 11.
15. The alkaline water electrolysis device according to claim 14, comprising at least 6 electrocatalyst plates, and preferably each electrocatalyst plate has at least 0.5 m 2 , and preferably at least 1.5m 2 surface area.
Citation Information
Patent Citations
Mining method and use of mined material in production of graphene and graphitic material
US20180179648A1